Prisoners discharged from Tasmanian prisons 1865-1874 - Finnane, Mark (ADA Dataverse, 2021)
Prisoners discharged from Tasmanian Prisons, 1865-1874, data accessed from Tasmanian Police Gazette. Data includes name, offence, sentence, trial date and place, date of discharge from prison, prisoner descriptions including height, age, birthplace, occupation. The data was originally transcribed for the ARC funded project Corn Stalks and New Chums, Crime and Nutritional Status in Settler Australia, DP140102231 and has subsequently been curated by the Prosecution Project.